Synthesis and utilization of siderophores by Shigella flexneri. - Payne, S M (1980)
Strains of Shigella flexneri secrete a hydroxamate-type siderophore when grown in low-iron media. This hydroxamate appears to be identical with aerobactin, a siderophore synthesized by Aerobacter aerogenes. In contrast to other enteric bacteria, S. flexneri did not produce detectable phenolate siderophores, although it could utilize an exogenously supplied phenolate.